GAYA KOMUNIKASI MUBALIGH DALAM SOROTAN PUBLIK - YULISTA, YERA (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2016)
When preaching preachers will use a variety of communication styles. Communication style is a set of behaviors that can be used communicator (preachers) in conveying the message to get a certain response in certain situations anyway. Style of communication in the form of verbal and nonverbal language may be spontaneous or its use should be regulated in such a way that the purpose of the communication itself can be achieved. The figure of the preacher as a public figure is implicitly demanded by the public can provide exemplary through their behavior, then what would happen if at some time preachers bring communication styles that are considered unfit "owned / used" by them as a preacher ?, regard is the author tries to analyze the style mubaligh communication that into the public spotlight.